WO3 as Additive for Efficient Photocatalyst Binary System TiO2/WO3 - Knoks, Ainars; Kleperis, Janis; Bajars, Gunars; Grinberga, Liga; Bogdanova, Olga (Walter de Gruyter, 2021)
Two different methods of synthesis of TiO2/WO3 heterostructures were carried out with the aim to increase photocatalytic activity. In this study, anodic TiO2 nanotube films were synthesized by electrochemical anodization of titanium foil. WO3 particles were applied to anodic Ti/TiO2 samples in two different ways-by electrophoretic deposition (EPD) and insertion during the anodization process. Structural and photocatalytic properties were compared between pristine TiO2 and TiO2 with incorporated WO3 particles. Raman mapping was used to character-ise the uniformity of EPD WO3 coating and to determine the structural composition. The study showed that deposition of WO3 onto TiO2 nanotube layer lowered the band gap of the binary system compared to pristine TiO2 and WO3 influence on photo-electrochemical properties of titania. The addition of WO3 increased charge carrier dynamics but did not increase the measured photo-current response. As the WO3 undergoes a phase transition from monoclinic to orthorhombic at approximately 320 proper sequence WO3 deposition could be beneficial. It was observed that secondary heat treatment of WO3 lowers the photocurrent. © 2021 A. Knoks et al., published by Sciendo. This work is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License.
The financial support provided by Scientific Research Project for Students and Young Researchers No. SJZ/2018/9 implemented at the Institute of Solid State Physics, University of Latvia is greatly acknowledged. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the Euro-pean Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART².
Keywords: Research Subject Categories::NATURAL SCIENCES; Anodization; electrophoretic deposition; TiO2 nanotubes; thin films; TiO2/WO3; WO3